2009
DOI: 10.1007/s10900-009-9167-3
|View full text |Cite
|
Sign up to set email alerts
|

African American Men’s Understanding and Perceptions About Prostate Cancer: Why Multiple Dimensions of Health Literacy are Important in Cancer Communication

Abstract: Prostate cancer (PrCA) is the most diagnosed cancer among men in the United States, especially among African American (AA) men. The purpose of this formative study was to explore the implications of applying Nutbeam's multidimensional health literacy framework to AA men's understanding of PrCA information. Participants were 25 AA men aged 45 and older in South Carolina. Their functional health literacy was assessed using two modified Cloze tests and the Shortened Test of Functional Health Literacy in Adults (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 31 publications
6
104
0
2
Order By: Relevance
“…23 Further, health literacy tests may not capture the cultural attitudes, values, and beliefs that influence how a person receives and interprets information. 24 …”
Section: Discussionmentioning
confidence: 99%
“…23 Further, health literacy tests may not capture the cultural attitudes, values, and beliefs that influence how a person receives and interprets information. 24 …”
Section: Discussionmentioning
confidence: 99%
“…14 It also is well-documented that AAs' spiritual needs play a pivotal role in influencing their participation in research. 16,17 However, there had been no previous study on PrCA education and informed decision-making in South Carolina that included AA men and women.…”
Section: Informed Prostate Cancer Screening -Owens Et Almentioning
confidence: 99%
“…Studies have shown that ill-designed science communications can have no effect or can even lead to misunderstandings, misperceptions, and mistrust (34,35). Designers can forget that their audiences may not share the same scientific language, and therefore may misunderstand or tune out messages that include complex scientific language or visuals.…”
Section: Challenge 1: Agreeing On Goalsmentioning
confidence: 99%